TAK1 inhibition increases proliferation and differentiation of chick retinal cells - Carrillo, Casandra; Ravi, Vagisha; Tiwari, Sarika; Chernoff, Ellen A.; Belecky-Adams, Teri L. (Frontiers in Cell and Developmental Biology, 2022)
Coordination of the cell cycle with proliferation and differentiation is essential to obtain the right number of cells at the appropriate time during the development of the central nervous system. Cell cycle length, in particular the G1 phase of the cycle, has been coupled to differentiation in the central nervous system, but the mechanism as well as the reason behind an increase in the length of the cell cycle are unclear. Previous studies have proposed that the length of the G1 phase is a critical determinant in the accumulation of differentiation factors in progenitor cells. The cell has a better chance of amassing factor(s) necessary for the differentiation process with a longer cell cycle. The studies herein focus on a potential role for transforming growth factor β-activated kinase 1 (TAK1), a hub kinase that lies at the intersection of multiple signaling pathways, in the coordination of proliferation, cell cycle exit and differentiation in the chick retina. Previous studies have focused predominantly on the role this kinase plays in the inflammation process and axonal growth. TAK1 is downstream of multiple signaling pathways that are critical to development of the central nervous system, including transforming growth factor β (TGFβ), bone morphogenetic proteins (BMPs), and WNTs. The present study indicates that activated TAK1 is found throughout the developing retina; however, it is localized at higher levels in dividing and differentiating cells. Further, ex ovo retinal studies using TAK1 inhibitor 5Z-7-oxozeaenol increased both progenitor and differentiating cell populations, accompanied by a substantial increase in proliferation and a smaller increase in cell death. These results indicate that TAK1 may be involved in cell cycle progression.